Mud Volcano in Southeast Maluku: Evidence for Neotectonics in East Indonesia - Zaim, Yahdi; Ernawan, Budi; Fachrizal, Fachrizal (Ikatan Ahli Geologi Indonesia, 2012)
Mud volcanoes are observed in S.E. Maluku, east Indonesia, in Babar, Tanimbar and in the Kai islands. They are active, show bubbles of flammable gases, mud flows and rock fragments, and except in the Kai Islands, are associated with melange complexes. They have also been reported to be present on Timor Island. The formation of active mud volcanoes in S.E. Maluku is closely related to the geology and tectonics of this region, and is due to subsurface overpressures forming liquefied shale that is extruded along thrust faults and fractured zones. The association of melange complexes and Quaternary fractured limestone terraces with mud volcanoes is closely related to the Quaternary and neotectonic activities in this region. Mud volcanism in this region is probably one of the main processes leading to the formation of chaotic deposits in the Quaternary in SE Maluku.